Respon Pertumbuhan dan Produksi Bawang Merah (Allium ascalonium L.) Terhadap Pupuk NPK - Laia, Jeprianus; Harahap, Rahmaniah; Miyarnis, Miyarnis (UNIVERSITAS LABUHANBATU, 2024)
North Sumatra is shallots. Shallot (Allium ascolonicum L.) is a horticulture that has many benefits for people's lives, both from economic value and nutritional content, so that shallot production increases every year and is proven based on BPS (Central Statistics Agency) for the last 5 years. The effort needed to meet the needs of shallot production is to increase soil productivity, using the addition of NPK fertilizer. This study used factorial randomized group design (RAK). For accuracy in this study, it was repeated 3 times. namely: NPK fertilizer (N) with 3 levels, namely: N0 = Control, N1 = 5 g/plant, and N2 = 10 g/plant. The results of the Anova Variance test showed that the response of NPK fertilizer treatment to plant height 3 mst, 4 mst, 5 mst, 6 mst and wet weight of tubers per plot (g) had a significant effect, but the observation of the number of tubers per sample plant (tubers), and the diameter of tubers per sample (mm) had no significant effect. Keywords: NPK fertilizer, NPK dosage, and shallots